"Thanks for hearing me out": Voices of social work students during COVID-19. (March 2021) - Cole, Sarah J; Mitra, Samantha S; Robinson, Jennifer A; Jen, Sarah; Paceley, Megan S; Carr, Kortney A; Riquino, Michael; Wright, Kelechi
Abstract: As social work educators and students, the COVID-19 pandemic impacted our teaching and learning in challenging ways. We embarked on a qualitative research study to better understand the ways in which the pandemic was affecting the social work students in our program. Three faculty mentors worked collaboratively with five social work students across BSW, MSW, and PhD programs to interview 66 BSW and MSW students about their experiences, challenges, and hopes during the early months of the pandemic. BSW and MSW students led the analysis and early dissemination for the project. This essay describes the unique experiences of social work students by using a research poem to capture the emotional and experiential aspects of the students we interviewed.